WOMEN, POWER AND THE ECONOMY collective feminist practice can transform the world. - KUENKEL, INCA PETRA (ROUTLEDGE, 2026)
In the complex landscapes of multiple global crises, the book unfolds as a panoramic journey through the intricate pathways of women and power, weaving a tapestry that transcends crises and ushers in a transformative vision of a just world.Against the backdrop of a patriarchal history steeped in autocratic power practices, the author urges us to recognize, understand and redefine power in its myriad forms for collective feminist power practices. With meticulous analysis, she unveils challenges posed by the patriarchal backlash, exposing the normalized male definitions of power and the societal structures that sustain pathological power relationships. The narrative of the book intertwines power, economy and patriarchy, laying bare the many traps for complicity with the patriarchal systems. The author advocates for a paradigm shift, emphasizing the role of female memories and genealogies as foundational elements for a collective feminist practice. Power, in this context, emerges not as a force for dominance but as the ability to make a positive impact, flourishing in the rich diversity of differences. The envisioned future is one where societies thrive on commons, planetary care, feminist economies and pluriversality. The narrative charts a course toward a feminist democracy, rooted in nurturing the planet and safeguarding future generations. Governance and networks stand as keystones in shaping these utopian landscapes, where pioneers and movements play vital roles in sculpting the contours of tomorrow.The book offers practical tools for strengthening collective feminist practices that can restructure power pathologies. It unfolds as a captivating vista, where the echoes of the past harmonize with the aspirations of a feminist future.